The adventures of John Blake. Mystery of the ghost ship - Pullman, Philip, 1946- (Graphix, 2017)
Due to a research experiment gone wrong, John Blake is doomed to sail the seas on the time-traveling ship "Mary Alice," traveling between centuries in search of a way back to his own time and home. In the present time, Serena Anderson, a wealthy Australian teen, gets lost at sea and rescued by the "Mary Alice." Learning about John's predicament, Serena finds herself caught up in a deadly game of cat and mouse on the high seas as John tries to stay one step ahead of the powerful Dahlberg Corporation, whose leader is after John's time-traveling power for his own nefarious purposes.